THE PARAMETER ANALYSIS OF CUBICAL STRUCTURED CADMIUM TELLURIDE (CdTe) SEMICONDUCTOR MATERIALS - Sinta Puspita Apriliani; Susi Susilawati; Koharudin Koharudin; Sarah Nabilah; Dwi Lestariningsih; Witri Desmulyani; Anis Munir Rukyati; Muhammad Fikri Fakhrurozi; Stefiana Sondary Az Zahrah; Irmansyah Irmansyah; Irzaman Irzaman (Spektra: Jurnal Fisika dan Aplikasinya, 2021)
Cadmium telluride (CdTe) semiconductor materials will be used to analyze the energy gap, lattice parameters, and error value of these cubical structured crystal materials. The data that we used to be analyzed is using data from the International Center for Diffraction Data (ICDD) that used the X-ray Diffraction (XRD) method. This research has been successfully analyzing energy gap, lattice parameters, and the error value of Cadmium telluride (CdTe) materials which have a cube-shaped crystal structure. The result of the gap energy analysis of Cadmium telluride (CdTe) with a cubical structure yields a value of 1.43 eV. The lattice parameters of Cadmium telluride (CdTe) with a cubical structure analyzed by the Cramer-Cohen method yields a value of a = b = c = 9.922 Å. The error value of Cadmium telluride (CdTe) with a cubical stcucture yields a value of 6.75 x 10-4 %.